Magnetic metal nanoparticle-loaded nitrogen-doped wood carbon aerogel wave-absorbing material and preparation method thereof
By growing metal-organic complexes in situ in natural wood pores, forming nitrogen-doped wood carbon aerogel absorbing material loaded by magnetic metal nanoparticles, the problems of uneven distribution of magnetic particles and complex processing procedures are solved, and efficient electromagnetic wave absorption performance is achieved.
Patent Information
- Application Number
- CN202411808450.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-18
AI Technical Summary
The existing carbon-based magnetic composite materials have problems such as uneven distribution of magnetic particles, complex processing procedures and high manufacturing costs, and it is difficult to effectively solve the impedance matching problem of electromagnetic wave absorption.
Natural wood is used as raw materials, and metal-organic complexes are grown in situ in the wood channel through solvothermal reaction to form nitrogen-doped wood carbon aerogel absorbing material loaded by magnetic metal nanoparticles, achieving uniform dispersion and loading of magnetic nanoparticles.
This material has excellent electromagnetic wave absorption performance. The thickness of the nitrogen-doped wood carbon aerogel absorber material loaded by magnetic metal Co nanoparticles can reach an optimal reflection loss of -70.43dB at 2.4mm, and has an effective absorption bandwidth of 3.30GHz.
Smart Images

Figure CN119637846A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electromagnetic wave absorbing materials, and specifically relates to a nitrogen-doped wood carbon aerogel absorbing material loaded with magnetic metal nanoparticles and a preparation method thereof. Background Art
[0002] In recent years, non-metallic materials with light weight and high conductivity have been regarded as the most promising electromagnetic wave absorption materials. Among them, carbon-based materials are widely used in the field of electromagnetic wave absorption due to their high conductivity and low density. However, due to the poor impedance matching between carbon and air in carbon-based materials, their high conductivity and internal dense structure often cause electromagnetic waves to tend to be reflected and cannot be absorbed, thereby polluting the environment.
[0003] In order to solve this problem, wood-based carbon materials have the advantages of high porosity, low density, light weight and large specific surface area, which can effectively optimize impedance matching. In addition, carbon-based composite materials loaded with magnetic substances have the effect of enhancing the magnetic attenuation of electromagnetic waves. However, carbon-based magnetic composite materials often have problems such as uneven distribution of magnetic particles, complex processing procedures, and high manufacturing costs, which still need to be further solved. Summary of the invention
[0004] In order to overcome the problems existing in the above prior art, the purpose of the present invention is to provide a nitrogen-doped wood carbon aerogel absorbing material loaded with magnetic metal nanoparticles and a preparation method thereof, which uses natural wood with a directional multi-level pore structure as a raw material, and in-situ grows a metal-organic complex in the wood pores through a solvent thermal reaction. The purpose is to achieve uniform dispersion and loading of magnetic nanoparticles in wood carbon-based materials, thereby solving the problems of structural inhomogeneity and complex processing procedures in the preparation of absorbing materials.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is:
[0006] A method for preparing a nitrogen-doped wood carbon aerogel absorbing material loaded with magnetic metal nanoparticles comprises the following steps:
[0007] Step 1: Delignify the cut natural wood and then freeze-dry it to obtain delignified wood aerogel;
[0008] Step 2: reacting the delignified wood aerogel with a metal adenine solution in a reactor, followed by freeze drying to obtain a wood aerogel loaded with a metal adenine complex;
[0009] Step 3: subjecting the wood aerogel loaded with the metal adenine complex to high-temperature carbonization treatment in an inert gas to obtain a nitrogen-doped wood carbon aerogel absorbing material loaded with magnetic metal nanoparticles.
[0010] In the step 1, the natural wood is cut into thin slice structures with a longitudinal length of 3 to 5 cm, a radial width of 2 to 4 cm, and a tangential height of 0.3 to 0.8 cm, and the natural wood is balsa wood.
[0011] The specific preparation process of delignified wood aerogel is as follows:
[0012] The cut natural wood slices were immersed in a 2wt% NaClO2 aqueous solution and the pH value was adjusted to 4-5 with glacial acetic acid. The solution was then heated to 100-120°C and reacted for 12-16 hours to remove most of the lignin. The sample from which most of the lignin had been removed was then repeatedly soaked and washed with deionized water to remove the residual solution from the reaction, and then freeze-dried for 2 days to obtain delignified wood aerogel.
[0013] In step 2, the preparation process of the metal adenine solution is as follows:
[0014] 2 mmol of adenine was added to 100 mL of DMF, heated and stirred at 140° C. on a magnetic stirrer until the adenine was completely dissolved and cooled to room temperature, and then a mixed iron cobalt salt of cobalt acetate tetrahydrate and ferrous acetate (1.5 mmol each) was added to dissolve to obtain the iron cobalt salt / adenine solution.
[0015] The molar mass ratio of cobalt acetate tetrahydrate to ferrous acetate in the iron-cobalt salt is 0:1 to 1:0.
[0016] In step 2, the mass ratio of delignified wood aerogel to iron cobalt salt / adenine is 3:1 to 2:1. The reaction conditions of the reactor are 120 to 140° C. for 3 to 5 hours, and the freeze-drying time is 2 days. The in-situ synthesis of adenine-metal complex helps to uniformly load the metal sites in the wood aerogel.
[0017] In step 3, the inert gas is argon.
[0018] In step 3, the carbonization temperature is 900-1000°C, the heating rate is 4-6°C / min, and the carbonization time is 2-3 hours. The carbonized aerogel makes the entire material have excellent conductivity. At the same time, the doping of nitrogen atoms will introduce defect polarization, graphitized nitrogen will help to improve dielectric loss, pyridine and pyrrole nitrogen can promote dipole relaxation loss, and play a vital role in improving the electromagnetic absorption capacity of the material.
[0019] The nitrogen-doped wood carbon aerogel absorbing material loaded with magnetic metal nanoparticles has a "honeycomb" porous structure. A large number of metal nanoparticles grow in the pores of the wood aerogel. The size of the porous structure is 20μm, and the size of the metal nanoparticles is 200nm.
[0020] Nitrogen-doped wood carbon aerogel absorber loaded with magnetic metal nanoparticles is used in the field of electromagnetic wave absorption.
[0021] The nitrogen-doped wood carbon aerogel absorber loaded with magnetic metal Co nanoparticles can achieve an optimal reflection loss of -70.43dB when the thickness is 2.4mm, and has an effective absorption bandwidth of 3.30GHz.
[0022] The nitrogen-doped wood carbon aerogel absorber loaded with magnetic metal Fe nanoparticles can achieve an optimal reflection loss of -55.3dB when the thickness is 2.5mm, and has an effective absorption bandwidth of 2.28GHz.
[0023] The nitrogen-doped wood carbon aerogel absorber material loaded with magnetic metal FeCo nanoparticles can achieve an optimal reflection loss of -47.9 dB when the thickness is 2.1 mm, and has an effective absorption bandwidth of 3.85 GHz.
[0024] Beneficial effects of the present invention:
[0025] The present invention uses natural wood as raw material, and through in-situ self-assembly reaction and high-temperature carbonization process, retains the "honeycomb-like" directional multi-level pore structure of natural wood, while giving the biomass carbon material good electrical conductivity and dielectric properties. Wood aerogel is obtained by delignification of natural wood, and then solvent thermal reaction is carried out with metal salts and adenine molecules, so that the metal-adenine complex is in-situ grown in the multi-level pores inside the wood aerogel, and finally a nitrogen-doped wood carbon aerogel absorber loaded with metal nanoparticles is prepared. The multi-level pore structure inside the nitrogen-doped wood carbon aerogel is not only conducive to the uniform distribution of cobalt nanoparticles, but its "honeycomb-like" porous structure is also conducive to optimizing the transmission path of electromagnetic waves. The introduction of metal nanoparticles increases the magnetic loss of the absorber, and high-temperature carbonization further increases the dielectric loss of the absorber. The coordination of adenine and metal can effectively inhibit the aggregation of metal ions, which is conducive to the dispersion of metal ions, so that the magnetic metal is evenly distributed. At the same time, the doping of nitrogen atoms will introduce defect polarization, and graphitized nitrogen helps to improve the dielectric loss.
[0026] The nitrogen-doped wood carbon aerogel absorber loaded with magnetic metal nanoparticles showed excellent electromagnetic wave absorption performance, among which the nitrogen-doped wood carbon aerogel absorber loaded with magnetic metal Co nanoparticles could achieve an optimal reflection loss of -70.43dB when the thickness was 2.4mm, and had an effective absorption bandwidth of 3.30GHz. The nitrogen-doped wood carbon aerogel absorber loaded with magnetic metal Fe nanoparticles could achieve an optimal reflection loss of -55.3dB when the thickness was 2.5mm, and had an effective absorption bandwidth of 2.28GHz. The nitrogen-doped wood carbon aerogel absorber loaded with magnetic metal FeCo nanoparticles could achieve an optimal reflection loss of -47.9dB when the thickness was 2.1mm, and had an effective absorption bandwidth of 3.85GHz. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a scanning electron microscope (SEM) image of the nitrogen-doped wood carbon aerogel absorbing material loaded with magnetic metal FeCo nanoparticles obtained in Example 3 of the present invention.
[0028] Figure 2 This is a transmission electron microscope (TEM) image of the nitrogen-doped wood carbon aerogel absorbing material loaded with magnetic metal FeCo nanoparticles obtained in Example 3 of the present invention.
[0029] Figure 3 It is an X-ray diffraction (XRD) diagram of the nitrogen-doped wood carbon aerogel absorbing material loaded with magnetic metal nanoparticles obtained in Examples 1-3 of the present invention.
[0030] Figure 4 It is a curve diagram showing the change of reflection loss of the coaxial sample of the nitrogen-doped wood carbon aerogel absorbing material loaded with magnetic metal Co nanoparticles obtained in Example 1 of the present invention as a function of frequency.
[0031] Figure 5 It is a curve diagram of the reflection loss of the coaxial sample of the nitrogen-doped wood carbon aerogel absorbing material loaded with magnetic metal Fe nanoparticles obtained in Example 2 of the present invention as a function of frequency.
[0032] Figure 6 It is a curve diagram showing the change of reflection loss of the coaxial sample of the nitrogen-doped wood carbon aerogel absorbing material loaded with magnetic metal FeCo nanoparticles obtained in Example 3 of the present invention as a function of frequency.
[0033] Figure 7 Schematic diagram of the curve showing the change of reflection loss of the sample with frequency. DETAILED DESCRIPTION
[0034] The present invention will be further described in detail below in conjunction with the accompanying drawings.
[0035] Embodiment 1:
[0036] Step 1: Add 950mL of water to a 1000mL beaker, weigh 20g of NaClO2 and add it to the beaker, take 13mL of glacial acetic acid to adjust the pH value, wait for the NaClO2 to completely dissolve, and then add 5g of balsa wood flakes. Place the beaker in an oil bath and heat it to 110°C, react for 12 hours, then take out the delignified wood chips and repeatedly soak and wash them with deionized water, remove the residual solution of the reaction and freeze for 2 hours, then freeze dry it in a freeze dryer for 2 days, and finally obtain delignified wood aerogel.
[0037] Step 2: Add 1.35g of adenine and 100mL of DMF solution to a round-bottom flask, place the round-bottom beaker in an oil bath and heat to 140°C, the speed reaches 2000rpm, react for 1 hour to obtain an adenine solution, wait for the solution to cool to room temperature, add 0.75g of cobalt acetate tetrahydrate and stir evenly to obtain a Co adenine solution. The Co adenine solution and a piece of delignified wood aerogel in step 1 are transferred to the reactor and reacted at 140°C for 4 hours. After the reaction is completed, the wood chips are removed and washed with deionized water, and the residual solution is removed and frozen for 2 hours, followed by freeze drying in a freeze dryer for 2 days to obtain a wood aerogel loaded with Co adenine complex.
[0038] Step 3: Place the wood aerogel loaded with Co adenine complex obtained in step 2 in an alumina crucible and put it into a tubular furnace. Heat it to 1000°C at a heating rate of 5°C / min in an argon atmosphere and keep it warm for 2 hours to obtain nitrogen-doped wood carbon aerogel loaded with magnetic metal Co nanoparticles.
[0039] Embodiment 2:
[0040] Step 1: Add 950mL of water to a 1000mL beaker, weigh 20g of NaClO2 and add it to the beaker, take 13mL of glacial acetic acid to adjust the pH value, wait for the NaClO2 to completely dissolve, and then add 5g of balsa wood flakes. Place the beaker in an oil bath and heat it to 110°C, react for 12 hours, then take out the delignified wood chips and repeatedly soak and wash them with deionized water, remove the residual solution of the reaction and freeze for 2 hours, then freeze dry it in a freeze dryer for 2 days, and finally obtain delignified wood aerogel.
[0041] Step 2: Add 1.35g of adenine and 100mL of DMF solution to a round-bottom flask, place the round-bottom beaker in an oil bath and heat to 140°C, the speed reaches 2000rpm, react for 1 hour to obtain an adenine solution, wait for the solution to cool to room temperature, add 0.52g of ferrous acetate and stir evenly to obtain an Fe adenine solution. Move the Fe adenine solution and a piece of delignified wood aerogel in step 1 to the reactor and react at 140°C for 4 hours. After the reaction is completed, remove the wood chips and wash them with deionized water, remove the residual solution of the reaction and freeze for 2 hours, then freeze-dry in a freeze dryer for 2 days to obtain a wood aerogel loaded with Fe adenine complex.
[0042] Step 3: Place the Fe adenine complex-loaded wood aerogel obtained in step 2 in an alumina crucible and put it into a tubular furnace. Heat it to 1000°C at a heating rate of 5°C / min in an argon atmosphere and keep it warm for 2 hours to obtain nitrogen-doped wood carbon aerogel loaded with magnetic metal Fe nanoparticles.
[0043] Embodiment 3:
[0044] Step 1: Add 950mL of water to a 1000mL beaker, weigh 20g of NaClO2 and add it to the beaker, take 13mL of glacial acetic acid to adjust the pH value, wait for the NaClO2 to completely dissolve, and then add 5g of balsa wood flakes. Place the beaker in an oil bath and heat it to 110°C, react for 12 hours, then take out the delignified wood chips and repeatedly soak and wash them with deionized water, remove the residual solution of the reaction and freeze for 2 hours, then freeze dry it in a freeze dryer for 2 days, and finally obtain delignified wood aerogel.
[0045] Step 2: Add 1.35g of adenine and 100mL of DMF solution to a round-bottom flask, place the round-bottom beaker in an oil bath and heat to 140°C, the speed reaches 2000rpm, react for 1 hour to obtain an adenine solution, wait for the solution to cool to room temperature, add 0.38g of cobalt acetate tetrahydrate and 0.26g of ferrous acetate and stir evenly to obtain a FeCo adenine solution. Move the FeCo adenine solution and a piece of delignified wood aerogel in step 1 to the reactor and react at 140°C for 4 hours. After the reaction is completed, remove the wood chips and wash them with deionized water, remove the residual solution of the reaction and freeze for 2 hours, then freeze-dry in a freeze dryer for 2 days to obtain a wood aerogel loaded with FeCo adenine complex.
[0046] Step 3: Place the FeCo adenine complex-loaded wood aerogel obtained in step 2 in an alumina crucible and put it into a tubular furnace. Heat it to 1000°C at a heating rate of 5°C / min in an argon atmosphere and keep it warm for 2 hours to obtain nitrogen-doped wood carbon aerogel loaded with magnetic metal FeCo nanoparticles.
[0047] Comparative Example 1:
[0048] Step 1: Add 950mL of water to a 1000mL beaker, weigh 20g of NaClO2 and add it to the beaker, take 13mL of glacial acetic acid to adjust the pH value, wait for the NaClO2 to completely dissolve, and then add 5g of balsa wood flakes. Place the beaker in an oil bath and heat it to 110°C, react for 12 hours, then take out the delignified wood chips and repeatedly soak and wash them with deionized water, remove the residual solution of the reaction and freeze for 2 hours, then freeze dry it in a freeze dryer for 2 days, and finally obtain delignified wood aerogel.
[0049] Step 2: Add 1.35 g of adenine and 100 mL of DMF solution to a round-bottom flask, place the round-bottom beaker in an oil bath and heat to 140 ° C, the speed reaches 2000 rpm, and react for 1 hour to obtain an adenine solution. Move the adenine solution and a piece of delignified wood aerogel in step 1 to the reactor and react at 140 ° C for 4 hours. After the reaction, take out the wood chips and wash them with deionized water, remove the residual solution of the reaction and freeze them for 2 hours, then freeze-dry them in a freeze dryer for 2 days to obtain adenine-loaded wood aerogel.
[0050] Step 3: Place the adenine-loaded wood aerogel obtained in step 2 in an alumina crucible and put it into a tubular furnace. Heat it to 1000°C at a heating rate of 5°C / min in an argon atmosphere and keep it warm for 2 hours to obtain nitrogen-doped wood carbon aerogel free of magnetic metals.
[0051] Comparative Example 2:
[0052] Step 1: Add 950mL of water to a 1000mL beaker, weigh 20g of NaClO2 and add it to the beaker, take 13mL of glacial acetic acid to adjust the pH value, wait for the NaClO2 to completely dissolve, and then add 5g of balsa wood flakes. Place the beaker in an oil bath and heat it to 110°C, react for 12 hours, then take out the delignified wood chips and repeatedly soak and wash them with deionized water, remove the residual solution of the reaction and freeze for 2 hours, then freeze dry it in a freeze dryer for 2 days, and finally obtain delignified wood aerogel.
[0053] Step 2: Add 0.75 g of cobalt acetate tetrahydrate and 100 mL of DMF solution to the reaction bottle, wait until the cobalt acetate tetrahydrate is fully dissolved, add a piece of delignified wood aerogel in step 1, and then move the reaction solution to the reactor and react at 140°C for 4 hours. After the reaction is completed, take out the wood chips and wash them with deionized water, remove the residual solution of the reaction and freeze them for 2 hours, and then freeze-dry them in a freeze dryer for 2 days to obtain the wood aerogel loaded with Co adenine complex.
[0054] Step 3: Place the wood aerogel loaded with Co adenine complex obtained in step 2 in an alumina crucible and put it into a tubular furnace. In an argon atmosphere, heat it to 1000°C at a heating rate of 5°C / min and keep it warm for 2 hours to finally obtain a magnetic metal Co-loaded wood carbon aerogel without adding adenine.
[0055] Comparative Example 3:
[0056] The same as comparative example 2, except that: in step 2, 0.75 g of cobalt acetate tetrahydrate is replaced with 0.52 g of ferrous acetate, and then the same solvent thermal treatment as comparative example 2 is performed to obtain a magnetic metal Fe-loaded wood carbon aerogel without adding adenine.
[0057] Comparative Example 4:
[0058] The same as comparative example 2, except that: in step 2, 0.75 g of cobalt acetate tetrahydrate is replaced with 0.38 g of cobalt acetate tetrahydrate and 0.26 g of ferrous acetate, and then the same solvent thermal treatment as comparative example 2 is performed to obtain a wood carbon aerogel loaded with magnetic metal FeCo without adding adenine.
[0059] Test Example 1:
[0060] The magnetic FeCo metal nanoparticle-loaded nitrogen-doped wood carbon aerogel absorber prepared in Example 3 was tested by scanning electron microscopy (SEM) and transmission electron microscopy (TEM), and the images measured were as follows: Figure 1 and 2 shown.
[0061] Depend on Figure 1 It can be observed that the absorbing material presents a 3D porous honeycomb structure, which is the multi-level directional pore structure inherent in natural wood and is still retained after various treatments. The three-dimensional ordered porous network structure helps to enhance the multiple reflection loss of electromagnetic waves in the pores.
[0062] Figure 2 Metal nanoparticles loaded on the carbon material can be observed, and the metal nanoparticles are evenly distributed without large-area aggregation. The three-dimensional network wood aerogel structure with Fe / Co nanoparticles attached can produce a large number of heterogeneous interfaces, thereby increasing the interface polarization and conductive loss of the material.
[0063] Figure 3X-ray diffraction (XRD) test spectra of the nitrogen-doped wood carbon aerogel absorber loaded with magnetic metal nanoparticles prepared in Examples 1-3 are given. The peaks of the nitrogen-doped wood carbon aerogel sample loaded with metal Co nanoparticles at 44.2°, 51.6° and 75.8° correspond to the (111), (200) and (210) crystal planes of metal Co, confirming the presence of metal Co in the wood aerogel. The peaks of the nitrogen-doped wood carbon aerogel sample loaded with metal Fe nanoparticles at 45.1° and 65.2° correspond to the (110) and (200) crystal planes of metal Fe, confirming the presence of metal Fe in the wood aerogel. The diffraction peaks of metal Fe and Co appear simultaneously in the XRD spectrum of the nitrogen-doped wood carbon aerogel sample loaded with metal FeCo nanoparticles, confirming the presence of FeCo alloy in the nitrogen-doped wood carbon aerogel.
[0064] Figure 4 The hysteresis loop of the nitrogen-doped wood carbon aerogel absorbing material loaded with magnetic FeCo metal nanoparticles prepared in Example 3 is given. The electromagnetic wave absorbing material shows ferromagnetism, and the source of magnetism is due to the introduction of metal Fe and Co nanoparticles.
[0065] The nitrogen-doped wood carbon aerogel absorbing material loaded with magnetic metal Co nanoparticles prepared in Example 1 was taken for testing of its absorbing performance. Testing method for electromagnetic wave absorption performance: The powder of the nitrogen-doped wood carbon aerogel absorbing material loaded with metal Co and paraffin are mixed in a mass ratio of 1.5:8.5, i.e. a filling ratio of 15%, and pressed into a coaxial sample with an outer diameter of 7.00 mm, an inner diameter of 3.04 mm, and a thickness of about 2 mm in a special mold. A vector network analyzer is used to test the electromagnetic parameters of the sample at 2 to 18 GHz, and the absorbing performance is calculated. The curve of the reflection loss of the sample changing with frequency is shown in the figure below. Figure 5 shown. Figure 5 It is shown that when the matching thickness is 2.4 mm, the maximum absorption intensity reaches -70.4 dB, and the maximum effective absorption band (less than -10 dB) is 3.30 GHz wide. It can be seen that the nitrogen-doped wood carbon aerogel absorbing material loaded with magnetic metal Co nanoparticles prepared in Example 1 has strong absorbing performance.
[0066] The nitrogen-doped wood carbon aerogel absorbing material loaded with metal magnetic Fe nanoparticles prepared in Example 2 was tested for absorbing performance in the same manner as in Example 1. The curve of reflection loss of the sample changing with frequency is shown in FIG. Figure 6 shown. Figure 6 It is shown that when the matching thickness is 2.5 mm, the maximum absorption intensity reaches -55.3 dB, and the maximum effective absorption band (less than -10 dB) is 2.28 GHz. It can be seen that the nitrogen-doped wood carbon aerogel absorbing material loaded with metal magnetic Fe nanoparticles prepared in Example 2 has a strong absorbing performance.
[0067] The nitrogen-doped wood carbon aerogel absorbing material loaded with magnetic metal FeCo nanoparticles prepared in Example 3 was tested for absorbing performance in the same manner as in Example 1. The curve of reflection loss of the sample changing with frequency is shown in FIG. Figure 7 shown. Figure 7 It is shown that when the matching thickness is 2.1 mm, the maximum absorption intensity reaches -47.9 dB, and the maximum effective absorption band (less than -10 dB) is 3.85 GHz wide. It can be seen that the nitrogen-doped wood carbon aerogel absorbing material loaded with metal magnetic FeCo nanoparticles prepared in Example 3 has a strong absorbing performance.
Claims
1. A method for preparing a nitrogen-doped wood carbon aerogel absorbing material loaded with magnetic metal nanoparticles, characterized in that: The following steps are involved: Step 1: Delignify the cut natural wood and then freeze-dry it to obtain delignified wood aerogel; Step 2: reacting the delignified wood aerogel with a metal adenine solution in a reactor, followed by freeze drying to obtain a wood aerogel loaded with a metal adenine complex; Step 3: subjecting the wood aerogel loaded with the metal adenine complex to high-temperature carbonization treatment in an inert gas to obtain a nitrogen-doped wood carbon aerogel absorbing material loaded with magnetic metal nanoparticles.
2. The method for preparing a nitrogen-doped wood carbon aerogel absorbing material loaded with magnetic metal nanoparticles according to claim 1, characterized in that: In the step 1, the natural wood is cut into thin slice structures with a longitudinal length of 3 to 5 cm, a radial width of 2 to 4 cm, and a tangential height of 0.3 to 0.8 cm, and the natural wood is balsa wood.
3. The method for preparing a nitrogen-doped wood carbon aerogel absorbing material loaded with magnetic metal nanoparticles according to claim 1, characterized in that: The specific preparation process of delignified wood aerogel is as follows: The cut natural wood slices are immersed in a 2wt% NaClO2 aqueous solution and the pH value is adjusted to 4-5 with glacial acetic acid. The solution is then heated to 100-120°C and reacted for 12-16 hours to remove most of the lignin. The sample from which most of the lignin has been removed is then repeatedly soaked and washed with deionized water to remove the residual solution from the reaction, and then freeze-dried to obtain delignified wood aerogel.
4. The method for preparing a nitrogen-doped wood carbon aerogel absorbing material loaded with magnetic metal nanoparticles according to claim 1, characterized in that: In step 2, the preparation process of the metal adenine solution is as follows: 2 mmol of adenine is added to 100 mL of DMF, heated and stirred at 140° C. on a magnetic stirrer until the adenine is completely dissolved and cooled to room temperature, and then a mixed iron cobalt salt of cobalt acetate tetrahydrate and ferrous acetate is added to dissolve to obtain the iron cobalt salt / adenine solution, wherein the molar mass ratio of cobalt acetate tetrahydrate and ferrous acetate in the iron cobalt salt is 0:1 to 1:
0.
5. The method for preparing a nitrogen-doped wood carbon aerogel absorbing material loaded with magnetic metal nanoparticles according to claim 4, characterized in that: In the step 2, the mass ratio of delignified wood aerogel to iron cobalt salt / adenine is 3:1-2:1, the reaction conditions in the reactor are 120-140° C. for 3-5 hours, and the freeze-drying time is 2 days.
6. The method for preparing a nitrogen-doped wood carbon aerogel absorbing material loaded with magnetic metal nanoparticles according to claim 1, characterized in that: In step 3, the inert gas is argon; In the step 3, the carbonization temperature is 900-1000° C., the heating rate is 4-6° C. / min, and the carbonization time is 2-3 hours.
7. A nitrogen-doped wood carbon aerogel absorbing material loaded with magnetic metal nanoparticles prepared by the method according to any one of claims 1 to 6, characterized in that: It has a "honeycomb" porous structure, and a large number of metal nanoparticles grow in the pores of the wood aerogel. The size of the porous structure is 20μm, and the size of the metal nanoparticles is 200nm.
8. Application of the nitrogen-doped wood carbon aerogel absorbing material loaded with magnetic metal nanoparticles prepared by the method according to any one of claims 1 to 6, characterized in that: Nitrogen-doped wood carbon aerogel absorber loaded with magnetic metal nanoparticles is used in the field of electromagnetic wave absorption.
9. The use of the nitrogen-doped wood carbon aerogel absorbing material loaded with magnetic metal nanoparticles according to claim 8, characterized in that: The nitrogen-doped wood carbon aerogel absorber loaded with magnetic metal Co nanoparticles can achieve an optimal reflection loss of -70.43dB when the thickness is 2.4mm, and has an effective absorption bandwidth of 3.30GHz. The nitrogen-doped wood carbon aerogel absorber loaded with magnetic metal Fe nanoparticles can achieve an optimal reflection loss of -55.3dB when the thickness is 2.5mm, and has an effective absorption bandwidth of 2.28GHz. The nitrogen-doped wood carbon aerogel absorber material loaded with magnetic metal FeCo nanoparticles can achieve an optimal reflection loss of -47.9 dB when the thickness is 2.1 mm, and has an effective absorption bandwidth of 3.85 GHz.
Citation Information
Cited By
Three-dimensional oriented porous aerogel loaded with yttrium-cobalt nanoparticles as well as preparation method and application of three-dimensional oriented porous aerogel
CN121198174A